Technology-Integrated Catechism Curriculum: A Systematic Literature Review on Strengthening Youth Faith and Preventing Juvenile Delinquency - Rependi Sianturi; Darul Ilmi (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Negeri Jakarta, 2026)
This study addresses the increasing problem of juvenile delinquency among Indonesian youth, including church adolescents, by examining the need for a more relevant and transformative catechism curriculum. The research employs a qualitative systematic literature review of peer-reviewed articles on catechesis, Christian religious education, youth faith formation, and juvenile delinquency. The inclusion criteria covered publications from 2021 to 2025 in English and Indonesian; however, all selected studies were published between 2023 and 2025 due to their stronger relevance and methodological suitability. The findings indicate that effective catechism curricula must adopt a holistic, contextual, and participatory approach integrating theological perspectives, adolescent developmental psychology, and character education. In addition, this study highlights that the integration of educational technology—such as digital media, e-learning platforms, and interactive applications—is a critical component in enhancing engagement, accessibility, and learning effectiveness among digital-native youth. The proposed curriculum framework emphasizes contextual theological content, student-centered learning strategies, experiential spiritual practices, and sustainable mentoring supported by collaboration among church, family, and educational institutions. This study contributes theoretically by integrating faith formation and educational technology within a unified framework and practically by offering a technology-integrated catechism curriculum model to strengthen youth faith and moral resilience in addressing juvenile delinquency.